Description of the molecular and phenotypic spectrum in Chinese patients with aggrecan deficiency: Novel ACAN heterozygous variants in eight Chinese children and a review of the literature - Deng, Shuyun; Hou, Lele; Xia, Dan; Li, Xiaojuan; Peng, Xiaofang; Xiao, Xiaoqin; Zhang, Jieming; Meng, Zhe; Zhang, Lina; Ouyang, Nengtai; Liang, Liyang (Frontiers in Endocrinology, 2022)
Objective This study analyzed eight Chinese short stature children with aggrecan deficiency, and aimed to investigate potential genotype–phenotype correlations, differences in clinical characteristics between the Chinese and the Western populations, and effectiveness of recombinant human growth hormone therapy in patients with ACAN variants through a review of the literature. Methods Pediatric short stature patients with ACAN heterozygous variants were identified using whole-exome sequencing. Subsequently, a literature review was carried out to summarize the clinical features, genetic findings, and efficacy of growth-promoting therapy in patients with ACAN variants. Results We identified seven novel ACAN mutations and one recurrent variant. Patients in our center manifested with short stature (average height SDS: -3.30 ± 0.85) with slight dysmorphic characteristics. The prevalence of dysmorphic features in the Chinese populations is significantly lower than that in the Western populations. Meanwhile, only 24.24% of aggrecan-deficient Chinese children showed significantly advanced bone age (BA). Promising therapeutic benefits were seen in the patients who received growth-promoting treatment, with an increase in growth velocity from 4.52 ± 1.00 cm/year to 8.03 ± 1.16 cm/year. Conclusion This study further expanded the variation spectrum of the ACAN gene and demonstrated that Chinese children with short stature who carried ACAN heterozygous variants exhibited early growth cessation, which may remain unnoticed by clinicians as most of these children had very mild dysmorphic characteristics and showed BA that was consistent with the chronological age. Genetic testing may help in the diagnosis.